In- and off-season academic performance of college student-athletes in team sports - Valleser, Christian Wisdom M. (Asia Life Sciences : the Asian International Journal of Life Sciences, 2014)
Varsity sports is a part of many colleges and universities in the Philippines. At the core of any collegiate sports program is the student-athlete. The purpose of this study was to determine how changes in the competitive environment may influence the academic performance of college student-athletes in team sports. This is the first time such an endeavor was attempted in the Philippine setting. The researcher compared the General Weighted Averages (GWA) and academic credits attempted during the in- and off- seasons by student-athletes from the University of the Philippines Diliman. A total of 221 college student-athletes from three team sports - basketball, football, and volleyball - were included in the study. Overall, there was no difference in the academic performance during the in-season and off-season GWA's. A separate analysis yielded similar results for gender, team and sport. There was also no difference in academic load credits attempted during the in- and off- season overall and in separate analysis for gender, sport and team. This did not take into account load credits attempted during the summer term and it is likely that student-athletes enrolled in reduced academic load during the regular semesters and enrolled in the summer term to make up for academic credits. The academic performance of student-athletes was not affected by regular transitions between the in- and off-seasons.